Malaysian professionals' beliefs in child sexual abuse disclosure - Nen, Salina; Subhi, Nasrudin; Mohamad, Mohd Suhaimi; Jusoff, Kamaruzaman; Chong, Sheau Tsuey; Sarnon @ Kusenin, Norulhuda; Mohd Hoesni, Suzana; Wan Jaafar, Wan Azreena (IDOSI Publications, 2011)
This study explores factors that influence professionals' belief on child victim's disclosure of sexual abuse. This study was conducted on 18 professionals who worked with child sexual abuse (CSA) cases included counsellors, medical social workers, social workers and police officers. Findings indicate that factors such as victim's age, trauma symptoms, delay disclosures, signs of abuse and corroborate information from others (e.g. family members, schoolmates, friends, teachers) were all influenced professionals beliefs on victim's disclosure. The results also indicate the presence of CSA myths were evident among professionals. This suggests the importance of disseminating accurate information. As such, incorrect beliefs may influence professionals' perceptions and responses to victims' disclosure.